The Temperature Dependence of the Energy Gap of CdGeP2 Semiconductor - Omer, M. S.; Karim, A. S.; Yousif, S. O. (Sulaimani Journal for Pure and Applied Sciences, 2001)
The theoretkal method of Fan and shocklyaitardeen is used to cakulate the temperature dependence of the energy gap in the temperature range (300 — 425 Ki for the ternary semiconducting compound CdGeri2. the results are (L63-1 .71 )100.01 eV in the temperature -range mentioned above and they are in good agreement with those of the reported experimental work The temperature variation of AEg and Eg were discussed in terms of the effects of the electron = phonon interaction and the lattice dilation The effect of the lattice expansion is larger than that of the lattice vibration, but both effecis „ for this compound ,. are found to be linear with T for the rtempitattirre make investigateci The empirical relation of ( Prarshni„ Ravin.. dra Srivastava and Seehra Sehra) is also wed to calcultikie Eg versus T It gives good results in comparison with the reported experimental work „ as well as with the calculated results.
Keywords: Semiconductors; CdGePi; Energy gap; Lattice vibration Lattice dilation A Special Issue Devoted To Papers Presented in Tire First Scientific Conference of Zoinkcy Sulaimant 2728th 5E062000 Part of his MSc Thesis